The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1365-2591.2006.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of oral bacteria to 254 nm ultraviolet light

Abstract: The application of UV light to eliminate endodontic pathogens may be possible. Nevertheless, its absorbance by outer layers of bacteria should be considered and the UV light dose adapted accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
7
20
1
Order By: Relevance
“…Interestingly, all the strains revealed UV resistance, since the fraction of each population killed by 254 nm irradiation was in the range of 0-5% at 60 J.m -2 , 60-70% at 80 J.m -2 , 95-98% at 100 J.m -2 and 99.5-99.9% at 120 J.m -2 . This is to be compared to the reported 100% killing of Lactobacillus brevis exposed to 254 nm UV light at 70 J.m -2 [47]. Competition experiments in mixed cultures revealed no imbalance in growth or survival between the σ H overproducing or σ H deficient and WT strains in MCD medium (Figure 5).…”
Section: Resultsmentioning
confidence: 57%
“…Interestingly, all the strains revealed UV resistance, since the fraction of each population killed by 254 nm irradiation was in the range of 0-5% at 60 J.m -2 , 60-70% at 80 J.m -2 , 95-98% at 100 J.m -2 and 99.5-99.9% at 120 J.m -2 . This is to be compared to the reported 100% killing of Lactobacillus brevis exposed to 254 nm UV light at 70 J.m -2 [47]. Competition experiments in mixed cultures revealed no imbalance in growth or survival between the σ H overproducing or σ H deficient and WT strains in MCD medium (Figure 5).…”
Section: Resultsmentioning
confidence: 57%
“…The conclusion is that the application of UV light to eliminate endodontic pathogens may be possible. Nevertheless, its absorbance by outer layers of bacteria should be considered and the UV light dose adapted accordingly (13).…”
Section: S S U E 2 2 0 1mentioning
confidence: 99%
“…Photodynamic therapy (PDT) and ultraviolet disinfection both use light at a specified wavelength that is known to have antimicrobial properties (Metzger et al 2007, Chrepa et al 2014). The most current endodontic research is focusing on PDT as a potential adjunctive debridement technique.…”
Section: Advances In Irrigation and Disinfection Of The Root Canalmentioning
confidence: 99%
“…In a recent systematic review on PDT, Chrepa et al found that all 57 studies included in the review "showed positive effect of PDT in the reduction of microbial load in root canal treatment ranging from 91.3% -100%." The PDT is showing positive results in the eradication of bacteria from the canal space, but, this treatment does not come without disadvantages; such as tooth discoloration due to the photosensitizer and potential for wide range cytotoxicity (Chrepa et al 2010 (Metzger et al 2006 and).…”
Section: Advances In Irrigation and Disinfection Of The Root Canalmentioning
confidence: 99%
See 1 more Smart Citation